1999
DOI: 10.1063/1.371057
|View full text |Cite
|
Sign up to set email alerts
|

Thermally induced conduction type conversion in n-type InP

Abstract: n-type semiconducting InP is changed into p-type semiconducting by short time annealing at 700 °C. Further annealing for a longer time leads to a second conduction-type conversion changing the material back to n type again but with a much higher resistivity. These conduction conversions indicate the formation of both acceptor and donor defects and the progressive variation of their relative concentrations during annealing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Its electronic properties can be easily tuned using different dopants, thus make it show either n- or p-type behavior. Many reports can be found on the electronic behaviors studies of InP films or bulk InP crystals. However, the electronic transport of 1D InP nanostructures was seldom investigated. Previously, Lieber et al reported the n- or p-type tuning of InP nanowires by introducing different dopants .…”
Section: Resultsmentioning
confidence: 99%
“…Its electronic properties can be easily tuned using different dopants, thus make it show either n- or p-type behavior. Many reports can be found on the electronic behaviors studies of InP films or bulk InP crystals. However, the electronic transport of 1D InP nanostructures was seldom investigated. Previously, Lieber et al reported the n- or p-type tuning of InP nanowires by introducing different dopants .…”
Section: Resultsmentioning
confidence: 99%
“…Hence, for the improvement of their selectivity, functionalization processes are required in many cases. 27 It was shown that these conduction conversions are related to the formation of acceptor defects that are responsible for the rst p-type conversion, and donor defects that cause the second n-type conversion. Abdelhalim and co-workers examined the response of a CNTbased gas sensor functionalized with Au, toward different ammonia concentrations, varying from 10-100 ppm.…”
Section: Introductionmentioning
confidence: 99%
“…26 Simultaneously, in recent years, carbon-based materials have been evaluated from the viewpoint of their transition from ntype to p-type materials, and their second conversion to n-type, upon annealing. 27 It was shown that these conduction conversions are related to the formation of acceptor defects that are responsible for the rst p-type conversion, and donor defects that cause the second n-type conversion. It has also been reported that graphene nanoribbons under functionalization by nitrogen species through high-power electrical joule heating in ammonia exhibit n-type electronic doping.…”
Section: Introductionmentioning
confidence: 99%